2011
DOI: 10.12659/msm.881435
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the cytotoxicity of FotoSan™ light-activated disinfection on human fibroblasts

Abstract: SummaryBackgroundRoot canal disinfection needs to be improved because actual techniques are not able to eliminate all microorganisms present in the root canal system. The aim of the present study was to investigate the in vitro cytotoxicity of FotoSan (CMS Dental APS, Copenhagen Denmark), 17% EDTA and 2% chlorhexidine.Material/MethodsFibroblasts of periodontal ligament from healthy patients were cultured. FotoSan (with and without light activation for 30 sec.), 17% EDTA and 2% chlorexidine were used for the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…It also presented the same antimicrobial potential than the clinically used classical irrigants, CHX and EDTA. It is worth mentioning that TBO (Seal et al, 2002; Bergmans et al, 2008; Rios et al, 2011) is available in the market under the name of Fotosan ® agent (Gambarini et al, 2011; Rios et al, 2011) and RB has been widely studied (Shrestha et al, 2012, 2014; Persadmehr et al, 2014). As expected, 3% NaOCl had the best final outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It also presented the same antimicrobial potential than the clinically used classical irrigants, CHX and EDTA. It is worth mentioning that TBO (Seal et al, 2002; Bergmans et al, 2008; Rios et al, 2011) is available in the market under the name of Fotosan ® agent (Gambarini et al, 2011; Rios et al, 2011) and RB has been widely studied (Shrestha et al, 2012, 2014; Persadmehr et al, 2014). As expected, 3% NaOCl had the best final outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…40 CHX can induce apoptotic and necrotic/autophagic cell death. 40,41 Studies showed that endothelial cells and fibroblasts are sensitive to CHX, but osteoblasts are the most sensitive cells. 40 Gambarini et al 41 demonstrated that the cytotoxic effect of MB on PDL fibroblasts (whether inactive or activated with a light source) was equal to that of ethylenediaminetetraacetic acid (EDTA) 17% and much lower than the toxicity of 0.3% CHX.…”
Section: Discussionmentioning
confidence: 99%
“…Such slight toxicity is not related to light-activated reactive oxygen species. 41 For evaluation of a therapeutic agent, two aspects must be considered: efficacy and safety, which are both important. Every nontoxic compound is not necessarily safe.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Several studies have shown that the dose required to cause bacterial death is lower the dose needed to cause damage to keratinocytes and fibroblasts. [14][15][16][17] Xu et al [18] suggested that PDT can be used as an adjunct to endodontic disinfection without damaging the cells of periapical region in their evaluation of the in vitro effects of methylene blue at 50 µg/mL and irradiation with diode light amplification by stimulated emission of radiation (LASER) at 665 nm for 5 min on human gingival fibroblasts and osteoblasts.…”
Section: Principles Of Activationmentioning
confidence: 99%